“There is no other option; we have to feed our families…who else would do it?”: The Financial Lives of Women Engaging in Sex Work in Ulaanbaatar, Mongolia - Tsai, Laura Cordisco (Canadian Center of Science and Education, 2013)
INTRODUCTION: This article provides an overview of the financial lives of women (n = 204) engaging in sex work in Ulaanbaatar, Mongolia. METHODS: This paper presents findings from a computer-based, interviewer-administered baseline assessment administered with women recruited for participation in a randomized controlled trial testing the feasibility of a combined HIV risk reduction and savings-led microfinance intervention for women engaging in sex work in Mongolia. FINDINGS: Findings demonstrate that most women are the primary financial providers for their households, using an array of earning strategies to provide for themselves and other dependents, with sex work often constituting the primary household income source. Financial instability in the lives of people engaging in sex work may increase their risk for HIV and STIs due to a compromised ability to negotiate safer sex with partners in times of economic crisis or need. High levels of financial responsibility for household welfare, when combined with low reported savings, the presence of debt, higher premiums offered for sex without a condom, and high levels of harmful alcohol use, may heighten women's risk for HIV and other STIs. CONCLUSION: Further research that documents the financial lives of people working in sex work is needed in order to understand the complex relationship between financial stability and engagement in sex work, and to inform the development and testing of structural HIV prevention interventions which target the economic determinants of risk. These findings highlight the importance of economic support programming for women engaged in sex work in Mongolia at a time of rapid economic change in Mongolia.